CHALLENGES FOR UNIVERSITY POLICY IN LITHUANIA - Ritzen, Jo; Želvys, Rimantas (Acta Paedagogica Vilnensia, 2014)
Following its newly won independence, Lithuania at first experienced a substantial decline in the per capita GDP. However, from there on Lithuania has been part of the “convergence” machine of the European Union, meaning that its economic growth rates are much higher than those of the richer European countries. However, if Lithuania wants a convergence to continue, then a serious overhaul of the system of higher education is required. It should focus on the employability of graduates. Universities can only engage in this overhaul if they are empowered – financially and managerially.The labour market has drastically changed over recent decades in all countries. The supply of graduates increased markedly, yet the demand increased faster, with the result that in most countries graduates have had a larger wage increase and a lower relative unemployment than those with less education. Under the cloak of increased demand for graduates, there is also a shift in the types of traits graduates need in order to function well in society. So how best to reinvent universities, to take on board the principle of graduates with the twenty-first-century skills as their prime output? Lithuania should have its own strategy, and it will not be easy to get it implemented, because educational change is perhaps among the most difficult to achieve.Continental European higher education is for the most part publicly provided and financed. The role of government in determining the organisation and performance of universities has been the focus of the NGO Empower European Universities, which has compared thirty-two European countries. The study found that in 2008, in comparison with the other countries, Lithuanian universities had much less financial autonomy, a slightly lower level of policy autonomy, and higher than average organisational autonomy. Funding in the Lithuanian higher education is currently insufficient to retain qualified teachers and to provide sufficient room for student–teacher interaction. Research funding as a percentage of GDP is low when compared internationally. Lithuanian rates of participation in higher education, and of graduation, are above the European average, but the percentage of foreign students is low (1.3 per cent with a European average of 5.9 per cent). Some 84.8 percent of graduates were employed within three years of graduation in 2010. This is above the European average of 82.9 per cent. 22.4 per cent of the enrolled students graduated in 2010 (above the European average of 21.2 per cent). On these measures Lithuania does well. This is a marked contrast to its academic research, which is far below the European average according to all parameters we have introduced. These include the presence of Lithuanian universities among the top five hundred in the Jiao Tong ranking, the number of publications in top journals, the number of Marie Curie fellows, cooperation with the private sector, and ERC awards. Lithuania has a low level of labour productivity (a little more than half the average European level), a low percentage of knowledge workers and a corresponding low GDP per capita. This is likely to be in part due to the low level of university research.Our policy recommendation is that the ties between the ministries of education and science and of economic affairs should be strengthened. A serious attempt should be made to bring Lithuanian research up to world standards. The latter may require a considerable increase in investment. The challenge for Lithuanian higher education is to be more focused not only on what society needs in terms of graduate skills and in research but also on how this can be done with the limited resources available. The Lithuanian system of higher education should be diversified so as to match students’ potential talents with the university offerings. In Europe, almost eighty per cent of graduates feel that they work in an international environment. This calls for English to be used at least in Masters programmes, as well as for some internationally oriented Bachelor studies. Rather than spend money in political and economic cooperation on translators, we need to produce graduates who are fluent in English next to their mother tongue. A wider usage of the English language in university studies will create more favourable conditions for teacher and student exchange and will encourage young people from abroad to enter Lithuanian universities.
Keywords: universities; policy of higher education; empowerment